2017
DOI: 10.1111/1751-7915.12736
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and regulation of sorbicillin biosynthesis by Penicillium chrysogenum

Abstract: Summary Penicillium chrysogenum is a filamentous fungus that is used to produce β‐lactams at an industrial scale. At an early stage of classical strain improvement, the ability to produce the yellow‐coloured sorbicillinoids was lost through mutation. Sorbicillinoids are highly bioactive of great pharmaceutical interest. By repair of a critical mutation in one of the two polyketide synthases in an industrial P. chrysogenum strain, sorbicillinoid production was restored at high levels. Using this strain, the sor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 32 publications
(52 reference statements)
2
51
0
Order By: Relevance
“…purpureus 50 and T. reesei 41 , 51 . For instance, C. rosea is predicted to harbour orthologs of the sorbicillinoid family-type yellow pigment sorbicillin ( pks2 and pks12 ) gene cluster 52 , 53 , conserved and functionally active in several distantly related fungi such as Acremonium chrysogenum , P. chrysogenum , T. reesei , Chaetomium globosum and Colletotrichum graminicola 30 , 51 . In addition, C .…”
Section: Discussionmentioning
confidence: 99%
“…purpureus 50 and T. reesei 41 , 51 . For instance, C. rosea is predicted to harbour orthologs of the sorbicillinoid family-type yellow pigment sorbicillin ( pks2 and pks12 ) gene cluster 52 , 53 , conserved and functionally active in several distantly related fungi such as Acremonium chrysogenum , P. chrysogenum , T. reesei , Chaetomium globosum and Colletotrichum graminicola 30 , 51 . In addition, C .…”
Section: Discussionmentioning
confidence: 99%
“…LCMS chromatograms obtained from + sorABD transformants ( Figure 2G)d id not significantly differ from those for + sorAB transformants,thus indicating that 2a and 2bare the required substrates for SorD.T he observation of both 1a and 1b in these transformants indicates that SorD does not oxidize 1b to 1a as proposed by Derntl et al [21] Similarly, since the oxosorbicillinols 9aand 9bwere not observed in any of the chromatograms,SorD does not seem to have arole in oxidizing 2 to 9 as proposed by Guzmµn-Chµvez et al [22] This shows that SorD has two roles:d imerization of 2 to 3 and 4, which does not require oxidation of 2,a nd an independent role in oxidizing 2a/b to epoxides 10 a/b.…”
Section: Resultsmentioning
confidence: 50%
“…[20] Theonly other confirmed homologous sorbicillinoid BGC exists in T. reesei QM6a [21] and shares the three core genes sorA, sorB and sorC required for formation of 2 (Scheme 1E). [9,[20][21][22] The T. reesei BGC also encodes asecond FMO named SorD.D erntl et al [21] proposed that T. reesei SorD catalyses the oxidation of 1b to 1a (Scheme 1F). In contrast, Guzmµn-Chµvez et al [22] suggested that P. chrysogenum SorD catalyses the oxidation of 2a into oxosorbicillinol 9a (Scheme 1F), since increased amounts of 2a were produced by their DsorD strain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pyrogallol-type phenolic compounds have three adjacent hydroxyl groups on the same benzene ring, which enables their easy oxidation or autoxidation and also allows metal ion chelation, both characteristics contributing significantly to a wide range of biological activities [ 81 ]. Finally, sorbicillinoids are secondary metabolites with anti-inflammatory and antimicrobial activities produced by filamentous fungi [ 82 ].…”
Section: Discussionmentioning
confidence: 99%